Determination of exchange enthalpy and entropy parameters of the equation-of-state theory for poly(dimethyl siloxane) and some aromatic solvents by inverse gas chromatography - Cankurtaran, Ö; Yilmaz, F (JOHN WILEY & SONS LTD, 2000)
The specific retention volumes, V-g(o) of toluene, ethyl benzene, n-propyl benzene and isopropyl benzene on poly(dimethyl siloxane)(PDMS) were measured at temperatures between 333 and 403K by inverse gas chromatography. The parameters of hard-core interaction, chi(t)(infinity), effective exchange energy, (X) over bar(12), exchange enthalpy, X-12, and exchange entropy, Q(12), in the equation-of-state theory were determined. The parameters chi(t)(infinity) of the isopropyl benzene-PDMS pair decreased from 0.65 to 0.60 while those of others decreased from around 0.77 to 0.69 with increasing temperature. The values of the parameters X-12 also decreased as molecular weight of the substituted aliphatic group on the benzene ring of the solvent increased, ie 15J cm(-3) in toluene and 5Jcm(-3) in isopropyl benzene. Both X-12 and Q(12) show negligible dependence on temperature. (C) 2000 Society of Chemical industry.
Keywords: poly(dimethyl siloxane); polymer-solvent interactions; equation-of-state parameters; inverse gas chromatography; INTRINSIC-VISCOSITY; THERMODYNAMICS; BENZENE; Polymer Science